The Influence of Digital Leadership and Online Training on Employee Performance Through Job Satisfaction in a Hybrid Work Environment at the BPJS Ketenagakerjaan Sumbagut Office - Meirizka Miranda Nasution; Prihatin Lumbanraja; Yeni Absah (Journal of Business Management, 2026)
This study aims to analyze the influence of digital leadership and online training on employee performance through job satisfaction in a hybrid work environment at the BPJS Ketenagakerjaan Sumbagut Regional Office. Digital transformation and the implementation of a hybrid work system require organizations to strengthen technology-based leadership as well as employee competency development in order to maintain optimal performance. This research uses a quantitative approach with a survey method. The research sample was determined using a purposive sampling technique, with a total of 81 employees as respondents. The data analysis method used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that digital leadership has a positive and significant effect on both job satisfaction and employee performance. Online training also has a positive and significant effect on job satisfaction and employee performance. Furthermore, job satisfaction is proven to have a positive and significant effect on employee performance. The indirect effect testing indicates that job satisfaction is able to significantly mediate the influence of digital leadership and online training on employee performance. These findings suggest that strengthening digital leadership and designing relevant and interactive online training can improve job satisfaction, which in turn enhances employee performance in a hybrid work environment. The implications of this study emphasize the importance of developing digital competencies for both leaders and employees, as well as optimizing online training systems that are aligned with job needs in order to support productivity and service quality in public sector organizations.